Integrating Students with Learning Disabilities into Regular Classrooms - Majadley , Enas (International Journal of Membrane Science and Technology, 2023)
This study investigates integrating a student with learning disabilities into regular classrooms. The research involved interviewing eight inclusion teachers who worked with this student for one academic year. Through this study, the researcher sought to gain insight into the current situation, address the challenges of inclusion, and gather the perspectives of inclusion teachers working in integrated classrooms. The results of this research could help inform modern trends in inclusion education. The main promising finding is that the inclusion teachers' role is critical in aiding students with special needs to develop their social, educational, and cultural values. In addition, the study sheds light on the challenges that the teacher experienced and proposed recommendations to overcome them. The study recommended providing teachers with the proper training and support, encouraging teachers to create special plans for each student's needs, and encouraging parents to be involved in their child's education.